2020
DOI: 10.1039/d0bm00171f
|View full text |Cite
|
Sign up to set email alerts
|

A fluorinated low-molecular-weight PEI/HIF-1α shRNA polyplex system for hemangioma therapy

Abstract: RNAi technology targeting HIF-1α could benefit hemangioma therapy effectively and FPEI polyplexes which could inhibit the expression of HIF-1α at the translational level can provide a practicable strategy for clinical hemangioma treatment in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…These data indicated that the fluorinated LW‐PEI‐based cationic micelles mediated effective miRNA delivery to modulate the biological properties of NSCs via gene regulation. [ 25 ] We further conducted terminal deoxynucleotidyl transferase–mediated dUTP nick‐end labeling (TUNEL) assay to verify the apoptosis rate of NSCs under hypoxic conditions after miR‐210 upregulation. TUNEL analysis showed the apoptosis rate in vitro of miR mimi ‐SPIO/PEI‐F‐labeled NSCs was 11.9 ± 3.82%, which was markedly lower than that of unlabeled NSCs (24.82 ± 3.80%), Scr‐SPIO/PEI‐F‐labeled NSCs (23.69 ± 6.91%), and miR inh ‐SPIO/PEI‐F‐labeled NSCs (21.03 ± 3.60%) ( P < 0.05) (Figure 4d,e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicated that the fluorinated LW‐PEI‐based cationic micelles mediated effective miRNA delivery to modulate the biological properties of NSCs via gene regulation. [ 25 ] We further conducted terminal deoxynucleotidyl transferase–mediated dUTP nick‐end labeling (TUNEL) assay to verify the apoptosis rate of NSCs under hypoxic conditions after miR‐210 upregulation. TUNEL analysis showed the apoptosis rate in vitro of miR mimi ‐SPIO/PEI‐F‐labeled NSCs was 11.9 ± 3.82%, which was markedly lower than that of unlabeled NSCs (24.82 ± 3.80%), Scr‐SPIO/PEI‐F‐labeled NSCs (23.69 ± 6.91%), and miR inh ‐SPIO/PEI‐F‐labeled NSCs (21.03 ± 3.60%) ( P < 0.05) (Figure 4d,e).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorinated LW-PEI-based cationic micelles demonstrated effective gene delivery to target cells with high biosafety. [25] Thus, it seems to be an appropriate candidate mediating gene therapy to modulate the biological properties of NSCs. To obtain the miRNA-complexed MRI-visible nanomedicine, SPIO-loaded fluorinated LW-PEI (PEI-F) micelles (SPIO/PEI-F) were synthesized by self-assembly of SPIO and PEI-F. Then, miRNA was absorbed on the surface of the micelles via electrostatic interaction.…”
Section: Synthesis and Gene Transfer Of Theranostic Nanomedicinementioning
confidence: 99%
“…One of the practical challenges we face is that the majority of cationic polymer vectors have low efficiency and are unsafe . Some studies have reported that the functional modification of LMW PEI can effectively improve its nucleic acid delivery with high safety. For this reason, first, we synthesized RRCPP-based LMW PEI as a backbone and modified it with cholesterol, PEG, and RGD-conjugated R8. Due to PEG having the advantages of inhibiting the phagocytosis of phagocytes and prolonging the blood circulation time, PEGylation combined with cholesterol modification has long been a conventional means of nanoparticle development.…”
Section: Discussionmentioning
confidence: 99%
“…To address such problems, researchers have developed fluorinated polymeric carriers . Thanks to the strong hydrophobic and fluorophilic properties, fluorinated segments connected on the cationic polymers could stabilize polyplexes in physiological environments at low critical concentrations, defending them from destabilization caused by serum proteins and other negatively charged biomacromolecules. At the same time, while fluoropolymers have shown bioinert and antifouling properties, fluorinated polyplexes have exhibited improved serum tolerance without decreasing transfection efficiency. To deliver nucleic acids such as DNA, siRNA, miRNA, etc., synthetic modifications of polyamidoamine, poly­(ethylenimine), poly­(propylenimine), poly­(amino ester), polypeptides, and many other dendrimers with fluorinated agents have been developed to produce cationic fluorinated carriers.…”
Section: Applicationsmentioning
confidence: 99%